Corrosion Activity on CFRP-Strengthened RC Piles of High-Pile Wharf in a Simulated Marine Environment - Ning Zhuang; Yujue Zhou; Yeming Ma; Yingdi Liao; Da Chen (Advances in Materials Science and Engineering)
We report test results from an experimental study to investigate the effectiveness of carbon fiber-reinforced polymer (CFRP) against reinforcing steel bar corrosion. Twelve reinforced-concrete pile specimens of 180 mm square by 1,600 mm long were cast. Three pile specimens were corroded to 5% steel mass loss and then strengthened with CFRP sheets; four specimens were strengthened by using CFRP sheets, whereas the remaining five specimens were not strengthened. The specimens were placed in a simulated marine environment, and corrosion was induced by an impressed current technique. At different theoretical corrosion degrees, nondestructive tests were performed to investigate the corrosion activity of the pile specimens, and destructive tests were performed to determine reinforcing steel bar mass loss. Based on the findings, the effectiveness of the CFRP-strengthened RC piles under aggressive marine environmental conditions was established.